Fatigue, psychological and cognitive impairment following transient ischaemic attack and minor stroke: a systematic review. (23rd May 2014) - Moran, G. M.; Fletcher, B.; Feltham, M. G.; Calvert, M.; Sackley, C.; Marshall, T.
<x xml:space="preserve">Abstract</x> Transient ischaemic attack (TIA) and minor stroke are characterized by short‐lasting symptoms; however, anecdotal and empirical evidence suggests that these patients experience ongoing cognitive/psychological impairment for which they are not routinely treated. The aims were (i) to investigate the prevalence and time course of fatigue, anxiety, depression, post‐traumatic stress disorder(PTSD) and cognitive impairment following TIA/minor stroke; (ii) to explore the impact on quality of life (QoL), change in emotions and return to work; and (iii) to identify where further research is required and potentially inform an intervention study. A systematic review of MEDLINE, EMBASE, PSYCINFO, CINAHL, the Cochrane libraries and the grey literature between January 1993 and April 2013 was undertaken. Literature was screened and data were extracted by two independent reviewers. Studies were included of adult TIA/minor stroke participants with any of the outcomes of interest: fatigue, anxiety, depression, PTSD, cognitive impairment, QoL, change in emotions and return to work. Random‐effects meta‐analysis pooled outcomes by measurement tool. Searches identified 5976 records, 289 were assessed for eligibility and 31 studies were included. Results suggest high levels of cognitive impairment and depression post‐TIA/minor stroke which decreased over time. However, frequencies varied between studies. Limited information was available on anxiety, PTSD and fatigue. Meta‐analysis revealed that the measurement tool administered influenced the prevalence of cognitive impairment: Mini‐Mental State Examination 17% [95% confidence interval (CI) 7, 26]; neuropsychological test battery 39% (95% CI 28, 50); Montreal Cognitive Assessment 54% (95% CI 43, 66). There is evidence to suggest that TIA/minor stroke patients may experience residual impairments; however, results should be interpreted with caution because of the few high quality studies. Notwithstanding, it is important to raise awareness of potential subtle but meaningful residual impairments.